Strategi Guru Dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Dan Hadist Pada Mata Pelajaran Al-Qur’an Hadist Di Pondok Pesantren Nurul Hidayah Simatorkis Pasaman Timur - Fadhliani Fadhliani; Salmi Wati; Junaidi Junaidi; Nurhasnah Nurhasnah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research is based on problems encountered by the author in the field, especially at the Nurul Hidayah Islamic Boarding School, namely that the Al-Qur'an hadith subject teachers at the Nurul Hidayah Islamic Boarding School are quite good. Starting from the beginning of learning which reminds them of memorization by reading it together and memorizing the Al-Qur'an and Hadith at the beginning of each week's learning, it's just that students don't use the best possible time to memorize the Al-Qur'an and Hadith. The aim of this strategy is that it is hoped that it can improve the ability to memorize the Al-Qur'an Hadith of students at MTs Nurul Hidayah. This research is descriptive research and the type of research is field research. The research is located at the Nurul Hidayah Simatorkis Islamic Boarding School. The key informants were Al-Qur'an Hadith teachers and the supporting informants were class IX students at MTs Nurul Hidayah. The data collection techniques used by researchers are observation, interviews and documentation. The results of this research show that teachers in improving the memorization ability of students at MTs Nurul Hidayah use strategies, namely methods and techniques. The methods used by teachers in learning are the takrir method (repeating by rote), the kitabah method (writing) and the sima'i (listening) method and the technique is to use the teacher as an instructor in guiding students so that they can improve their ability to memorize Al-Qur'an Hadith at MTs Nurul Hidayah. And the things that a teacher considers in using strategies are seen from considerations related to the goals to be achieved, seen from considerations related to learning materials or materials, seen from considerations from the student's perspective.